Interaction Of Platelet Activating Factor Acetyl Hydrolase (Paf Ah) Enzyme In Gln281 To Arg281 Mutation Toward Paf And Its Molecular Dynamic - Jayarani Fatimah Putri; widodo .; Muhammad Saifur Rohman (Journal of Tropical Life Science, 2014)
Platelet Activating Factor Acetyl Hydrolase (PAF AH) or LpPLA2 is key enzyme in myocardial infarction catalyzes the sn-2 acetyl group of Platelet Activating Factor (PAF) into lyso PAF and acetate as non-potent inflammatory molecules. PAF AH plays a critical role in arterial plaque development of Coronary Artery Disease (CAD). A crystal structure of PAF AH complexes with other ligand and effects of amino acid alteration to protein plasma consequence have also been reported. Here we report on the result of molecular docking and Molecular dynamic (MD) simulation carried out for PAF AH wild type (WT)/PAF and mutant Q281R/PAF complexes. Docking result shown that amino acid residues on active site of Q281 PAF AH mutant have not recognized on PAF AH. Eelectrostatics and hydrophobic bonds significantly reduced in Q281R than wild type. In the 7500 ps MD simulation Q281R showed less dynamics than WT but enzymatic machinary of mutant Q281R was not interrupted during MD simulation as well as PAF AH wildtype. These findings clearly indicated the importance effect of mutant Q281R in PAF AH recognition to its substrate